2022
DOI: 10.1038/s41598-022-17074-6
|View full text |Cite|
|
Sign up to set email alerts
|

High-resolution surface water dynamics in Earth’s small and medium-sized reservoirs

Abstract: Small and medium-sized reservoirs play an important role in water systems that need to cope with climate variability and various other man-made and natural challenges. Although reservoirs and dams are criticized for their negative social and environmental impacts by reducing natural flow variability and obstructing river connections, they are also recognized as important for social and economic development and climate change adaptation. Multiple studies map large dams and analyze the dynamics of water stored i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 58 publications
0
50
1
Order By: Relevance
“…The derived reservoir water area estimations are limited by the spatial coverage and accuracy restrictions of the initial dataset. As such, three available global water area products are developed by using algorithms that reclassify contaminated pixels as water, i.e., the GRSAD (Zhao & Gao, 2018), the RealSAT (Khandelwal et al, 2022), and areas of medium-small reservoirs by Donchyts et al (2022). These products cover only a portion of the reservoirs we studied (e.g., 908 overlapping reservoirs between GRSAD and our product) and use different algorithms and source datasets (e.g., RealSAT and GRSAD use only Landsat).…”
Section: Data and Methodology For Generating Reservoir Water Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The derived reservoir water area estimations are limited by the spatial coverage and accuracy restrictions of the initial dataset. As such, three available global water area products are developed by using algorithms that reclassify contaminated pixels as water, i.e., the GRSAD (Zhao & Gao, 2018), the RealSAT (Khandelwal et al, 2022), and areas of medium-small reservoirs by Donchyts et al (2022). These products cover only a portion of the reservoirs we studied (e.g., 908 overlapping reservoirs between GRSAD and our product) and use different algorithms and source datasets (e.g., RealSAT and GRSAD use only Landsat).…”
Section: Data and Methodology For Generating Reservoir Water Areamentioning
confidence: 99%
“…Hydroweb (Crétaux et al, 2011), G-REALM (Global reservoirs and lakes monitor, Birkett et al, 2011), DAHITI (Database for hydrological time series of inland waters, Schwatke et al, 2015), AltEx (Markert et al, 2019), HydroSat (Tourian et al, 2022), Water level On VITO, and several studies (e.g., Gao et al, 2012;Tortini et al, 2020;Shen et al, 2022b) offer time series of altimetry-derived water level for inland waters by incorporating multiple laser or radar altimeters such as Jason-1/2/3, CryoSat-2, Sentinel-3A/B, and ICESat-1/2. Imagery-based water area estimates can be extracted from GSW (Global surface water, Pekel et al, 2016), DAHITI, Hydroweb, HydroSat, Bluedot Observatory, GRSAD (Global reservoir surface area dataset, Zhao & Gao, 2018), RealSAT (Khandelwal et al, 2022), and relevant studies (e.g., Busker et al, 2019;Liu et al, 2021;Donchyts et al, 2022). Storage anomalies are available in DAHITI, HydroSat, and several studies (e.g., Gao et al, 2012;Hou et al, 2022) using water level and area from satellite altimeters and images, and/or from imagery-based water area and the area-storage model constructed by digital elevation model (DEM, Vu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we applied the new algorithm developed by Donchyts et al (2022a) to leverage freely accessible Landsat and Sentinel-2 images to generate reservoir water area time series. The Google Earth Engine (GEE) code for this water mapping algorithm is available at https://github.com/ global-water-watch/research-reservoir-water-dynamics (last access: 15 October 2022) and was applied individually to each reservoir and every satellite image intersecting a given reservoir to map accurate reservoir water.…”
Section: Surface Area Datasetsmentioning
confidence: 99%
“…This algorithm can efficiently address several challenges associated with optical Landsat satellites, such as contamination from clouds and limitations of previous algorithms that reclassify contaminated pixels as water. Donchyts et al (2022a) demonstrated the algorithm's good performance in mapping reservoir water areas by comparing the areas with in situ water level/storage in 768 reservoirs of varying size and geographic regions. Here, we detail how this algorithm addresses the challenges from optical images and generates a water area time series.…”
Section: Surface Area Datasetsmentioning
confidence: 99%
See 1 more Smart Citation